Cytogenetic Mapping of rRNAs and Histone H3 Genes in 14 Species of Dichotomius ( Coleoptera, Scarabaeidae, Scarabaeinae) Beetles - Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Moura, R. C.; Martins, C. [UNESP] (Karger, 2011)
Standard cytogenetic analyses and chromosomal mapping of the genes for 18S and 5S rRNAs and histone H3 were performed in 14 species of beetles of the genus Dichotomius (Coleoptera, Scarabaeidae, Scarabaeinae). Conserved karyotypes with 2n = 18 and biarmed chromosomes were observed in all species. Moreover, the presence of a large metacentric pair (pair 1) was characteristic in the studied species, evidencing a remarkable synapomorphy for this genus, which probably originated by an ancient fusion of 2 auto-somes while the ancestral sex-chromosome pair remained conserved. FISH showed that the 5S rRNA and histone H3 genes are located in the proximal region of pair 2, with the 2 genes co-located. However, the major rDNA cluster probed by the 18S rRNA gene mapped to 1-3 bivalents, being exclusively autosomal, associated with sex elements, or both. In most species, the major rDNA cluster was observed in pair 3, and it was frequently (64.3%) located in the distal region regardless of the chromosome. The conserved number and position of the 5S rDNA/H3 histone cluster seems to be an ancient pattern shared by all of the studied species. In contrast, the major rDNA clusters apparently tolerate distinct patterns of diversification in the karyotypes of the species that could be associated with small inversions, ectopic recombination, and transposition. Moreover, we reinforced the association/co-localization between the 5S rRNA and histone H3 genes in this group contributing thus to the knowledge about the chromosomal organization and diversification patterns of multigene families in beetles and insects. Copyright (C) 2011 S. Karger AG, Basel
Keywords: Chromosomal evolution; Fluorescence in situ hybridization; Multigene family; Scarabaeidae